Comparison of efficacy and safety of cilnidipine and losartan in patients of hypertension with or without diabetes from Gwalior, India - Bhalerao, Mayuri K.; Kothari, Saroj; Rastogi, Puneet (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Hypertension (HTN) is the most common cardiovascular disease. The objectives of present study are to investigate the comparison between cilnidipine and losartan with respect to changes in blood pressure (BP) and heart rate (HR) in hypertensive patients with or without type 2 diabetes mellitus (DM). Methods: We conducted a longitudinal, prospective, open labelled, comparative clinical study of hypertensive patients with or without type 2 DM. Of 161 enrolled hypertensives, 130 completed the study with follow up over a period of one year. Group I (n=34); and Group III (n = 32) patients with type 2 DM received cilnidipine 10-20mg orally OD. Group II (n =33); and Group IV (n = 31) patients with type 2 DM received losartan 50-100mg orally OD. The dosages were adjusted if the magnitude of reduction was insufficient. The parameters were monitored during follow – up at 4, 8 and 12 weeks. Results: Levels of systolic and diastolic BP and HR significantly decreased with both drugs. However, magnitude of HR reduction was greater with cilnidipine groups as compared to losartan groups with statistically significant difference (group I 70.79±9.21 versus group II 79.42±8.25, p = 0.000 and group III 76.25±7.08 versus group IV 81±7.15, p = 0.010). Of 161 patients, only 1 patient experienced hot flushes from group I. Conclusions: The present study demonstrated that therapy with cilnidipine can be used safely and effectively in hypertensive patients with or without diabetes. Cilnidipine was equally efficacious in lowering BP, while it more effectively reduced HR as compared to losartan. Cilnidipine can, therefore, be recommended as an alternative especially when there is associated tachycardia.